RELEVANSI PEMIKIRAN MUHAMMAD ABDUH TERHADAP SISTEM PENDIDIKAN DI PESANTREN - Sidiq Mustakim (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2016)
Sufism (Tasauf) Concept of Al-Ghazali which dominated in Islamic boarding school was being causal factor why didn’t the pupil or student too know about Muhammad Abduh. Abduh is a rational conceiver who considered that muslim’s deterioration caused by taklid. It was appropriate with his senior, Al-Afghani. Muhammad Abduh thought that it was caused by the stupidity doctrines, like adulating to syeikh, the teacher and others. Muhammad Abduh considered those doctrine would like to make the mind stops thinking, researching more about islam. Then, it was considered being in contradiction with culture and tradition in Islamic boarding school which all of pupil or student in Islamic boarding school have the highest obedient to their teacher.